2017
DOI: 10.1371/journal.pone.0176095
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy students' anxiety towards research during their undergraduate degree; How to reduce it?

Abstract: ObjectiveTo measure pharmacy students' anxiety towards research and how academic support, academic effort, attitude and self-efficacy influence their research anxiety.MethodsA cross-sectional study was conducted with undergraduate final year students of pharmacy using a convenient sampling method. A validated self-administered questionnaire was used.ResultsResponse rate for this study was 85.9% (128 students from a population of 149). The participants agreed that they read literature to understand research, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…These included good study habits and skills, good teachers' support for students; motivation, reducing workloads, improving cocurricular activities, and ensuring enough sleep and rest time. The results of the study concur with previous studies (Maharajan, et al, 2017;Mashayekh & Hashemi, 2011;Marszal-Wiśniewska, et al, 2011) where similar strategies were identified. Hence, a holistic approach needs to be sought and implemented to support the students cope with examination anxiety.…”
Section: Discussion Of Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These included good study habits and skills, good teachers' support for students; motivation, reducing workloads, improving cocurricular activities, and ensuring enough sleep and rest time. The results of the study concur with previous studies (Maharajan, et al, 2017;Mashayekh & Hashemi, 2011;Marszal-Wiśniewska, et al, 2011) where similar strategies were identified. Hence, a holistic approach needs to be sought and implemented to support the students cope with examination anxiety.…”
Section: Discussion Of Resultssupporting
confidence: 91%
“…Accordingly, it was inferred that motivation of students, reduction of subject load and good teacher support for students are crucial in reducing examination anxiety among students. This finding concurs with previous studies (Maharajan, et al, 2017;Mashayekh & Hashemi, 2011;Marszal-Wiśniewska, et al, 2011) but however disagrees with Arul (2014) who established no significant relationship between study habits and test anxiety of students.…”
Section: Discussion Of Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…9 Studying different research methods will help students improve their interpretation and application of clinical trial design and outcomes. 10 If students immerse themselves in multiprofessional research during the health professions curriculum, they will be able to collaborate more effectively with other providers upon their entry into practice.…”
Section: The Neuron Model In Ipe and Ebpmentioning
confidence: 99%
“…The expanded scope of pharmacy practice allows pharmacy graduates to start their professional lives in healthcare organisations in management, regulatory oversight, and pharmacy organisations, in addition to working in clinical and community practice (Taylor et al, 2015). Recent advancements in the field of pharmacy (Maharajan et al, 2017), the emergence of new treatments and evidence-based practice, make pharmacy an exciting and rewarding career; thus, pharmacy has become one of the most pursued professions in the healthcare field (Royal Pharmaceutical Society, 2018). Moreover, people frequently visit pharmacies and consult pharmacists for advice on health and wellbeing (Bates et al, 2016), with pharmacists being considered the most trusted professionals (Lynas, 2012).…”
Section: Introductionmentioning
confidence: 99%